Pain interference mediates the association between epigenetic aging and grip strength in middle to older aged males and females with chronic pain - Peterson, Jessica A.; Crow, Joshua A.; Johnson, Alisa J.; Meng, Lingsong; Rani, Asha; Huo, Zhiguang; Foster, Thomas C.; Fillingim, Roger B.; Cruz-Almeida, Yenisel (Frontiers in Aging Neuroscience, 2023)
Introduction Chronic pain is one of the leading causes of disability that may accelerate biological aging and reduce physical function. Epigenetic clocks provide an estimate of how the system ages and can predict health outcomes such as physical function. Physical function declines may be attributed to decreases in muscle quality due to disuse that can be measured quickly and noninvasively using grip strength. The purpose of this study was to explore the associations among self-reported pain, grip strength, and epigenetic aging in those with chronic pain. Methods Participants (57.91 ± 8.04 years) completed pain questionnaires, a blood draw and hand grip strength task. We used an epigenetic clock previously associated with knee pain (DNAmGrimAge), and used the subsequent difference of predicted epigenetic age from chronological age (DNAmGrimAge-Difference). Results Exploratory pathway analyses revealed that pain intensity mediated the association between DNAmGrimAge-difference and handgrip strength in males only (β = −0.1115; CI [−0.2929, −0.0008]) and pain interference mediated the association between DNAmGrimAge-difference and handgrip strength in males β = −0.1401; CI [−0.3400, −0.0222]), and females (β = −0.024; CI [−0.2918, −0.0020]). Discussion Chronic knee pain may accelerate epigenetic aging processes that may influence handgrip strength in older age adults. Chronic pain could be a symptom of the aging body thus contributing to declines in musculoskeletal function in later life.